STRUKTUR MODAL, PRODUKTIVITAS, DAN PROFITABILITAS SERTA CAPAIAN NILAI PERUSAHAAN - Muhamad Umar Mai (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2015)
The purpose of this study is to investigate and analyze: First, the effect of capitalstructure decisions towards the level of productivity of firm. Second, the effect of capitalstructure decisions and the level of productivity towards the company's profitability.Third, the effect of capital structure decisions and profitability towards achievements ofthe value of firm. This study conducted at the manufacturing companies went public inthe Indonesia Stock Exchange, with the observation period from 2010 to 2012.The results showed that the use of debt in the capital structure of firm is proxied totaldebt to total asset ratio (leverage) when controlled properly in the sense of caution orcare, it will have a positive impact to the profitability proxy return on equity and valueof the firm. is proxied price to book value. However, manufacturing firms are profitablein the period 2010 to 2012 in the Indonesia Stock Exchange has a strong tendency toreduce the portion of debt in their capital structure